Foundations of sustainable development - Reátegui Lozano, Rolando (2003)
This document aims to contribute to the debate and clarification on sustainable development, there is no sector in the world that does not speak of the importance of this topic, but very few understand what it really proposes. Capitalist countries and their representatives in different sectors repeatedly take advantage of this. Neoliberals also speak of sustainable development; But, are they consistent with its economic principles? Does the anthropocentric vision really propose sustainable development? In governments that are under the mandate of the IMF and WB, will policies that aim at sustainable development be implemented? These are some of the questions that we are going to clarify in the document. The environmental crisis is not a recent problem. This has been going on for many years. If in the 1970s the environmental crisis led to proclaiming the brake on growth before reaching ecological collapse, in the 1990s the dialectic of the environmental question has produced its negation: today the neoliberal discourse affirms the disappearance of the contradiction between environment and increase. Market mechanisms become the most accurate and effective way to internalize ecological conditions and environmental values ​​in the process of economic growth. In the neoliberal perspective, ecological problems do not arise as a result of capital accumulation, nor due to market failures, but because of not having assigned property rights and prices to common goods. Once this was established, the clairvoyant laws of the market would be in charge of adjusting ecological imbalances and social differences: equity and sustainability. The dominant discourse seeks to promote sustained economic growth, denying the ecological and thermodynamic conditions that set limits to the capitalist appropriation and transformation of nature. Nature is thus being incorporated into capital through a double operation: on the one hand, an attempt is made to internalize the environmental costs of progress; Along with this, a symbolic operation is implemented, a "calculation of significance" that recodes man, culture and nature as apparent forms of the same essence: capital. Thus, the ecological and symbolic processes are converted into natural, human and cultural capital, to be assimilated to the process of reproduction and expansion of the economic order, restructuring the conditions of production through economically rational management of the environment. In this way, the rhetoric of sustainable growth has turned the critical sense of the concept of environment into a voluntarist discourse, proclaiming that neoliberal policies must lead us towards the objectives of ecological balance and social justice by the most effective means: economic growth. guided by the free market. This discourse promises to achieve its purpose, without a foundation on the market's capacity to give its fair value to nature, to internalize environmental externalities and dissolve social inequalities; to reverse the laws of entropy and update the preferences of future generations.